Virtual reality and annotated radiological data as effective and motivating tools to help Social Sciences students learn neuroanatomy - Margot van Deursen (Nature Portfolio, 2021)
Abstract Neuroanatomy as a subject is important to learn, because a good understanding of neuroanatomy supports the establishment of a correct diagnosis in neurological patients. However, rapid changes in curricula reduced time assigned to study (neuro)anatomy. Therefore, it is important to find alternative teaching methods to study the complex three-dimensional structure of the brain. The aim of this manuscript was to explore the effectiveness of Virtual Reality (VR) in comparison with Radiological Data (RaD) as suitable learning methods to build knowledge and increase motivation for learning neuroanatomy. Forty-seven students (mean age of 19.47 ± 0.54 years; 43 females; 4 males) were included; 23 students comprised the VR group. Both methods showed to improve knowledge significantly, the improvement between groups was not different. The RaD group showed to have a significantly higher score on expectancy than students in the VR group. Task value scores regarding finding a task interesting, useful and fun were found to be significantly different in favor of the VR group. Consequently, significant higher Motivation scores were found in the VR group. Motivation and expectancy, however, did not moderate learning results, whereas task value impacted the results in favour of the VR group. This study concludes that VR and RaD are effective and diverting methods to learn neuroanatomy, with VR being more motivating than RaD. Future research should investigate motivation and task value when using VR over a longer period of time.